Transforming Survey Offices: Technology, Management and Coordination - Sapkota, Ram Kumar (Journal of Land Management and Geomatics Education, 2025)
This article tries to explore practical and innovative ideas to enhance service delivery, transparency, and efficiency in Survey Offices through low-cost, technology-driven, and coordination-based initiatives. It outlines how simple interventions in office management, good governance, record preservation, and the use of information technology-when integrated with proper collaboration and coordination can transform survey offices of the country. Without considering major legal or structural changes, the article emphasizes creativity, leadership, and the tactical use of existing resources to improve public satisfaction, streamline workflows, and promote good governance in Survey Offices. Through the suggested measures, Survey Offices can enhance public trust, accelerate service delivery, reduce procedural delays, and contribute to more accountable and citizen-focused cadastral services.